Case report: A rare case of omental extrarenal rhabdoid tumor and review of the literature - Li, Hui; Wen, Xiao-Hui; Fu, Xiao-Yun; Wu, Zuo-Hui (Frontiers in Oncology, 2024)
Extrarenal rhabdoid tumor of the greater omentum is extremely rare, with very rare, only sporadic reports and limited documentation of its ultrasonographic findings. Here, and its ultrasonographic findings are rarely reported. Here, we reportreport a case oase of extrarenal rhabdoid tumor of the greater omentum in a 16-year-old girl and review the relevant literature. It was found that the disease mainly occurred in female children and adolescents, mainly manifested as lower abdominal pain and a large abdominal cystic or solid hemorrhagic mass. The clinical characteristics include a high degree of malignancy and mortality. Ultrasound shows some malignant features, but it is not specific, so it is easy to be misdiagnosed in clinic., review the related literature, and discuss its clinical imaging features and differential diagnosis.